General Tolerance of Galactosyltransferases toward UDP‐galactosamine Expands Their Synthetic Capability. Issue 51 (9th November 2021) - Fu, Xuan; Gadi, Madhusudhan Reddy; Wang, Shuaishuai; Han, Jinghua; Liu, Ding; Chen, Xi; Yin, Jun; Li, Lei
Abstract: Accessing large numbers of structurally diverse glycans and derivatives is essential to functional glycomics. We showed a general tolerance of galactosyltransferases toward uridine‐diphosphate‐galactosamine (UDP‐GalN), which is not a commonly used sugar nucleotide donor. The property was harnessed to develop a two‐step chemoenzymatic strategy for facile synthesis of novel and divergent N ‐acetylgalactosamine (GalNAc)‐glycosides and derivatives in preparative scales. The discovery and the application of the new property of existing glycosyltransferases expand their catalytic capabilities in generating novel carbohydrate linkages, thus prompting the synthesis of diverse glycans and glycoconjugates for biological studies. Abstract : Preparation of diverse glycans is essential to glycobiology, while synthetically useful enzymes for this purpose are limited. This study discovered a general tolerance of galactosyltransferases (GalTs) toward uncommon donor UDP‐galactosamine. A two‐step strategy was devised to harness this property for the facile synthesis of GalNAc‐glycosides.